2021
DOI: 10.1186/s42155-020-00198-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial anaesthetics for pain control in arterial embolisation procedures: a systematic review and meta-analysis

Abstract: Purpose A systematic review to determine the effectiveness of intra-arterial anaesthetics on post- operative pain and opioid analgesia requirements in arterial embolisation procedures. Materials and methods A systematic review of the literature was performed (Embase, PubMed, MEDLINE and the Cochrane Library) from inception to 10th August 2020. Randomised controlled trials (RCTs) and cohort studies that utilised intra-arterial anaesthesia during an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The incidence of post-IR pain in cancer patients has not been studied in large cohorts. However, some studies have evaluated pain treatment after cementoplasties [ 5 ], embolization [ 6 ], and tumor ablation [ 14 ] and concluded that pain control was inadequate and that pain medications should be prescribed more liberally during and after tumor ablation [ 3 ] or percutaneous osteosynthesis [ 15 ]. As previously reported, the type of techniques used to treat tumors did not play a predominant role, and pain level and opiate consumption are comparable after radiofrequency and electroporation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of post-IR pain in cancer patients has not been studied in large cohorts. However, some studies have evaluated pain treatment after cementoplasties [ 5 ], embolization [ 6 ], and tumor ablation [ 14 ] and concluded that pain control was inadequate and that pain medications should be prescribed more liberally during and after tumor ablation [ 3 ] or percutaneous osteosynthesis [ 15 ]. As previously reported, the type of techniques used to treat tumors did not play a predominant role, and pain level and opiate consumption are comparable after radiofrequency and electroporation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…NVS from 0 to 4 (0, no pain; 1, low pain; 2, medium pain; 3, strong pain; and 4, excruciating pain) was measured in the PACU at least on arrival and exit, and the maximum score was retained for this study [ 6 ]. If the score could not be acquired because of consciousness impairment, the value was deemed non-evaluable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Intraarterial use of lignocaine (20-200 mg) into uterine arteries after embolization helps in the reduction of post-procedure pain for 7 hours (half-life of lignocaine 90-120 minutes) with reduced requirement of narcotic dose. 26 Superior hypogastric nerve block (SNBH) effectively reduces procedural pain and decreases the need for opioid analgesic. It is done by instilling 3 mL of 0.5% ropivacaine (75-100 mg) or 15-20 mL of 0.5% bupivacaine at the level below the abdominal aortic bifurcation (L5 level) and the anesthetic effect usually lasts for 8 to 12 hours.…”
Section: Pain Managementmentioning
confidence: 99%
“…26 A recent systematic review of various articles studying the use of intraarterial anesthesia in hepatic embolization and UAE showed that it may slightly reduce the intensity of pain and amount of postprocedural opiates used, but their results were not significant prompting the call for further study on its efficacy (►Table 2). 27 This technique is often favored by providers as it does not involve a second procedure and adds minimal time to the overall procedure.…”
Section: Local Anesthesiamentioning
confidence: 99%